Análisis de los efectos del estrés psicosocial en el entorno laboral sobre el sistema inmunológico en docentes universitarios. - Orosco Neira, Jordy Elian (My University, 2025)
Psychosocial stress in the university work environment represents a growing threat to the overall health of teaching staff. This study aimed to analyze the effects of psychosocial stress on the immune system in professors from the Faculty of Chemical and Health Sciences, as well as from other departments at the Technical University of Machala. A questionnaire based on the Maslach Burnout Inventory (MBI) model was administered to 61 professors, followed by hematological analysis for those who presented a moderate or high risk of burnout syndrome. The results indicated that 65.6% of the professors had a low level of risk, 18% moderate, and 16.4% high risk. Of the 21 professors at moderate and high risk, 15 agreed to undergo a white blood cell count analysis. The values obtained were: white blood cells 6.8×10³/μL, neutrophils 53.0%, lymphocytes 35.3%, and monocytes 7.6% all within the physiological range. Although no significant immunological alterations were detected, individual variations were observed that could be associated with sustained emotional exhaustion. The null hypothesis was validated, as no statistical evidence of a direct relationship between psychosocial stress and hematological changes was found. However, mild trends were identified in professors with greater emotional exhaustion and lower personal accomplishment, suggesting a possible subclinical immune response to prolonged stress. It was concluded that the study did not establish a statistically significant association between psychosocial stress and hematological alterations, thereby validating the null hypothesis. Nonetheless, the importance of further research with larger samples and complementary tests is recognized, to evaluate potential long-term effects. Additionally, the implementation of preventive strategies and emotional support programs aimed at the comprehensive well-being of teaching staff is recommended.
El estrés psicosocial en el entorno laboral universitario representa una amenaza creciente para la salud integral del personal docente. Este estudio tuvo como objetivo analizar los efectos del estrés psicosocial sobre el sistema inmunológico en docentes de la Facultad de Ciencias Químicas y de la Salud, así como de otros departamentos de la Universidad Técnica de Machala. A lo cual se aplicó el cuestionario basado en el modelo de Maslach Burnout Inventory (MBI), a 61 docentes, y posteriormente un análisis hematológico a quienes presentaron un riesgo moderado o alto de síndrome de burnout. Los resultados indicaron que el 65.6 % de los docentes presentó un nivel bajó, un 18 % moderado y el 16.4 % alto riesgo. De los 21 docentes con riesgo medio y alto, 15 accedieron al análisis de recuento leucocitario. Los valores obtenidos fueron: glóbulos blancos 6.8×10³/μL, neutrófilos 53.0 %, linfocitos 35.3 % y monocitos 7.6 %, todos dentro del rango fisiológico. Aunque no se detectaron alteraciones inmunológicas significativas, se observaron variaciones individuales que podrían asociarse a un desgaste emocional sostenido. La hipótesis nula se validó ya que al no encontrarse evidencia estadística de una relación directa entre el estrés psicosocial y cambios hematológicos. No obstante se identificó tendencias leves en docentes con mayor agotamiento emocional y baja realización personal, lo que sugiere una posible respuesta inmunológica subclínica ante el estrés prolongado. Se concluyó que el estudio no logró establecer una asociación estadísticamente significativa entre el estrés psicosocial y alteraciones hematológicas, validando la hipótesis nula. No obstante, se reconoce la importancia de profundizar en este tipo de investigaciones con muestras más amplias y pruebas complementarias, para evaluar posibles efectos a largo plazo. Como la implementación de estrategias preventivas y de acompañamiento emocional, orientadas al bienestar integral del personal docente.
Keywords: ESTRES PSICOSOCIAL; SISTEMA INMUNOLÓGICO; SALUD MENTAL; FATIGA